Participatory plant breeding to promote Farmers' Rights: October 2007 - Halewood, Michael; Deupmann, P.; Sthapit, B.R.; Vernooy, Ronnie; Ceccarelli, S. (2007)
The International Treaty on Plant Genetic Resources for Food and Agriculture (the Treaty) is the first legally binding international agreement that explicitly recognizes farmers' rights. The normative content of the Treaty's Article 9 on farmers' rights is relatively open-ended. It sets the scene for proactive and imaginative national-level implementation and for continued normative evolution at the international level by the Treaty's Governing Body. There are, of course, numerous potential complementary ways to promote farmers' rights. Perhaps the most commonly cited substantive element of farmers' rights is the right to save and exchange seed and the concomitant need to actively guard those rights through policy and legal means. Another commonly cited element is the right to earn benefits from the commercialization of farmers' varieties; adjusting national seed laws to allow the registration and commercialization of farmers' varieties would support farmers in this regard. These strategies are important and need to be supported. This brief seeks to raise the profile of participatory plant breeding (PPB) as an additional, complementary and powerful strategy for advancing the rights and interests of farmers.